Strategi Pemasaran Berbasis Digital: Membangun Hubungan Pelanggan yang Berkelanjutan pada Society 5.0 - Fathoni , Muhammad; Rusvitawati , Devi; Kasyfi , M. Farisan; Pamuja , Indra Agung (Paradoks : Jurnal Ilmu Ekonomi, 2025)
In Society 5.0, businesses face challenges in building sustainable customer relationships through digital-based marketing strategies. This research identifies the use of social media and digital platforms as having an important role in increasing customer loyalty as stated by (Nanda Annisa et al., 2020; Setiawan & Nurtjahjani, 2021). Researchers intend to explore effective digital marketing methods as well as factors that influence customer loyalty in the digital era. The method used is a literature review, collecting and analyzing various academic sources including recent journals and articles on digital marketing, online reputation, and customer loyalty. Digital technology provides opportunities for companies to offer more personalized experiences to customers (Sudirjo et al., 2023), while highlighting the importance of online reputation management in building trust(Asnita et al., 2024). Research shows that using digital marketing strategies can create close, sustainable customer relationships. Companies in Indonesia can drive customer loyalty and growth by providing relevant content, personalized interactions, and managing their reputation. This study provides practical recommendations for adapting to Society 5.0.